The Unique Neonatal NK Cells: A Critical Component Required for Neonatal Autoimmune Disease Induction by Maternal Autoantibody - Rival, Claudia; Setiady, Yulius; Samy, Eileen T.; Harakal, Jessica; Tung, Kenneth S. K. (Frontiers in Immunology, 2014)
Human maternal autoantibodies can trigger autoimmune diseases such as congenital heart block in the progeny of women with lupus or Sjogren’s disease. The pathogenic effect of early autoantibody exposure has been investigated in a murine neonatal autoimmune ovarian disease (nAOD) model triggered by a unique ZP3 antibody. Although immune complexes are formed in adult and neonatal ovaries, ZP3 antibody triggers severe nAOD only in <7 day-old neonatal mice. Propensity to nAOD is due to the uniquely hyper-responsive neonatal NK cells that lack the inhibitory Ly49C/I receptors. In nAOD, the neonatal NK cells directly mediate ovarian inflammation and oocyte depletion while simultaneously promoting de novo pathogenic ovarian-specific T cell responses. Resistance to nAOD in older mice results from the emergence of the Ly49C/I+ NK cells that regulate effector NK cells and from CD25+ regulatory T cell control. In preliminary studies, the ovarian resident FcgRIII+ macrophages and/or dendritic cells were found to be as indispensable players. Activated by ovarian immune complexes, they migrate to lymphoid organs where NK cell priming occurs. Remarkably, the findings in nAOD are very similar to those reported for neonatal responses to a retrovirus and its cognate antibody that lead to long-lasting immunity. Studies on nAOD therefore provide insights into maternal autoantibody-mediated neonatal autoimmunity, including congenital heart block, while simultaneously uncovering new properties of the neonatal innate and adaptive responses, lethality of premature infant infection, and novel neonatal antiviral vaccine design.